Autopsy-Based Study of Patterns of Head Injuries in Fatal Road Traffic Accidents in Kanpur District (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
The traumatic factor head injury due to road traffic accident (RTA) is a very common feature in the cases of fatal injuries, which is a permanent damage to lifetime just like a disease. In our study, the total autopsy conducted is 3730, in which males (58.32%) are out in number than females (41.68%). Total number of fatal head injury due to RTA is 1281 (34.34%). Most vulnerable age is 21–30 years comprising of 365 (28.49%) cases. On sex-wise comparison, 1013 (79.08%) males were injured than females (268 (20.92%)). Most of the incidents occurred between the time 1200 and 1800 hours comprising of 429 (33.49%) cases. Married victims are out in number comprising of 809 (63.15%) cases; 633 (49.42%) of victims died on the way to hospital, which is the highest, followed by 339 (26.46%) victims died in hospital, least number of deaths occur on the spot comprising of 309 (24.12%) cases. Two-wheeler occupants were the commonest group of victims comprising of 830 (64.79%) cases, pedestrian comprising 115 (8.98%) of total cases. Most common offending vehicle is heavy motor vehicle comprising 783 (61.12%) of all types of vehicle cases.
Keywords: Fatal injury; Pedestrian; Road traffic accident; Timing; Two-wheeler